Avaliação da política de saneamento básico em escolas públicas de Fortaleza - Galvão, Vitória Santana de Salles (2024)
The objective of this dissertation was to evaluate the public sanitation policy in public schools within the V Region of Fortaleza. The methodological approach included a literature review on the national sanitation policy and its historical development, supplemented by a documentary analysis of regulations and government reports. Technical visits were also conducted to several schools in the region to assess sanitation conditions, through semi-structured interviews with school administrators and the collection of qualitative data on the challenges faced. The results showed that, although the national sanitation policy has evolved over the years, its implementation still faces significant barriers in the V Region. A disparity was identified between legal guidelines and the actual conditions in schools, with frequent issues related to the lack of maintenance in sanitation facilities, intermittent water supply, and the absence of adequate wastewater systems. The research also revealed important gaps: there was a lack of systematized data on the impact of sanitation on students' health, as well as a lack of longitudinal analyses that would allow for correlating improvements in school sanitation with academic performance indicators. The analysis highlights that, to overcome the identified challenges, a coordinated effort is required between different levels of government, schools, and local communities. This dissertation contributes by presenting a detailed overview of the V Region and emphasizes the need for more effective and sustainable public policies to ensure dignified sanitation conditions in schools.